2012
DOI: 10.1007/s10948-012-1559-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Dependence of Blocking Temperature in Oleic Acid Functionalized Iron Oxide Nanoparticles

Abstract: We report the synthesis of phase pure, monodispersed Fe 3 O 4 nanoparticles of size ∼10 nm via chemical co-precipitation of ferrous and ferric ions, under controlled pH and temperature. The nanoparticles are oleic acid functionalized and hence dispersible in organic medium. The structure and morphology of nanoparticles are determined by analyzing XRD pattern and TEM micrographs, confirming the formation of phase pure Fe 3 O 4 nanoparticles. The magnetization studies reveal the superparamagnetic behavior of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…(1) where τ 0 is a characteristic of the material, named attempt time or attempt period (usually between 10 -10 -10 −9 s), K is the anisotropy constant, V is the volume of the nanoparticle, k B is the Boltzmann constant, and T is the temperature. Usually, at temperatures higher than the blocking temperature T B , that is the temperature below which the magnetic moments do not have the required energy to flip directions (for instance, T B is reported to be < 100 K, for oleic-acid stabilised SPIONs of ≈ 10 nm, when no external magnetic field is applied 17 ), and given the measuring times of conventional techniques, the net magnetisation of SPIONs results, on average, equal to zero. As evident from Eq.…”
Section: Spions and Their Interaction With Amfsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) where τ 0 is a characteristic of the material, named attempt time or attempt period (usually between 10 -10 -10 −9 s), K is the anisotropy constant, V is the volume of the nanoparticle, k B is the Boltzmann constant, and T is the temperature. Usually, at temperatures higher than the blocking temperature T B , that is the temperature below which the magnetic moments do not have the required energy to flip directions (for instance, T B is reported to be < 100 K, for oleic-acid stabilised SPIONs of ≈ 10 nm, when no external magnetic field is applied 17 ), and given the measuring times of conventional techniques, the net magnetisation of SPIONs results, on average, equal to zero. As evident from Eq.…”
Section: Spions and Their Interaction With Amfsmentioning
confidence: 99%
“…(for instance, T B is reported to be <100 K, for oleic-acid stabilised SPIONs of ≈10 nm, when no external magnetic field is applied 17 ), and given the measuring times of conventional techniques, the net magnetisation of SPIONs is, on average, equal to zero. As is evident from eqn (1), the smaller the nanoparticles, the lower the energy necessary to flip the magnetic moment.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Below this temperature, superparamagnetic MNPs immobilise in the absence of a magnetic field (H) [4]. T B varies between blocked state and superparamagnetic behaviour when H is changed; it possesses an inversely proportional relationship with H [22].…”
Section: Thermalmentioning
confidence: 99%
“…Moreover, the convergence of the ZFC and FC curves was not visible up to 380 K; therefore, both Sample 1 and the nanocomposites were in the blocked state (T B corresponded to the convergence point of both the ZFC and FC curves). It seemed that T B was outside of the measuring range, because we did not use any surfactant to decorate the γ -Fe 2 O 3 nanoparticles, in opposition to Kataby et al, who observed significant T B modifications depending on the surfactant used (e.g., stearic acid shifted T B to 280 K in relation to sulfonic acids, where T B was around 120 K) [ 79 ], as well as Tanwar et al, who showed that decoration of nanoparticles with oleic acid changed T B (from 95 K up to 15 K in the 0.5 T magnetic field) [ 80 ]. It should also be noted that in the case of surfactant-functionalized nanoparticles, the T B depends on the strength of the magnetic field.…”
Section: Resultsmentioning
confidence: 97%